2015
DOI: 10.1007/s13277-015-3563-3
|View full text |Cite|
|
Sign up to set email alerts
|

Regulation of metastasis of bladder cancer cells through the WNT signaling pathway

Abstract: Bladder cancer (BC) is the most popular malignant urinary cancer, with the highest incidence and mortality of all genitourinary system tumors worldwide. To date, the molecular regulation of the metastasis of BC remains ill defined. Here, we examined the levels of matrix metallopeptidase 9 (MMP9) and nuclear β-catenin in the BC specimen. We used lithium chloride (LiCl) to inhibit cytosol β-catenin phosphorylation and degradation to increase nuclear β-catenin levels in BC cells. We used IWP-2 to enhance cytosol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 34 publications
(45 reference statements)
1
18
0
Order By: Relevance
“…58 Therefore, LiCl has been widely used as a surrogate compound to assess the involvement of the Wnt/β-catenin pathway. [59][60][61][62][63][64] Interestingly, the current knowledge of the Wnt pathway can now explain clinical observation made even before the Wnt pathways have been described. Early case reports already demonstrated that treatment of patients suffering from chronic schizophrenia and asthma with LiCl not only reduced the manic episodes but also caused a reduction of asthma attacks and the use of asthma-specific medication, 65 and other clinical observations showed that stopping a long-lasting LiCl therapy in a patient-induced increased airway hyper-responsiveness and asthma symptoms.…”
Section: Immunological Role Of Wnt Pathways In Asthmamentioning
confidence: 99%
“…58 Therefore, LiCl has been widely used as a surrogate compound to assess the involvement of the Wnt/β-catenin pathway. [59][60][61][62][63][64] Interestingly, the current knowledge of the Wnt pathway can now explain clinical observation made even before the Wnt pathways have been described. Early case reports already demonstrated that treatment of patients suffering from chronic schizophrenia and asthma with LiCl not only reduced the manic episodes but also caused a reduction of asthma attacks and the use of asthma-specific medication, 65 and other clinical observations showed that stopping a long-lasting LiCl therapy in a patient-induced increased airway hyper-responsiveness and asthma symptoms.…”
Section: Immunological Role Of Wnt Pathways In Asthmamentioning
confidence: 99%
“…Dickkopf-1 (DKK1), a transcriptional target of the Wnt/ β -catenin pathway, functions as a negative regulator of Wnt signaling [9]. It has been reported that Wnt signaling inhibition by DKK1 limits the invasiveness of various types of cancer and that pathway activation by lithium chloride normally promotes cancer cell metastasis [911]. Accordingly, the Wnt/ β -catenin signaling pathway is considered an important regulator of cancer cell metastasis; therefore, more in-depth researches of the mechanisms that regulate the Wnt/ β -catenin pathway may provide a new perspective for more effective TSCC therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Here, miR-3713 is a novel number of the miRNA family and has not been reported of any direct targets, including MMP9. In our previous report, we have shown that MMP9 is a key regulator of TCC invasiveness, and the WNT signaling pathway seems to regulate TCC metastasis through activation of MMP912.…”
Section: Discussionmentioning
confidence: 94%
“…Nevertheless, the molecular pathway that regulates MMP9 activation has been shown to be different in different cancers. We recently reported that activation of WNT signaling pathway increased metastasis of TCC through activation of MMP912. However, the signal pathways to control MMP9 activation in TCC has not been completely clarified.…”
mentioning
confidence: 99%